Undiagnosed depressive and anxiety disorders in a nationally representative sample of Bangladeshi and Nepali women: prevalence and associated factors - Supa Pengpid; Karl Peltzer; M. Tasdik Hasan (International Journal of Mental Health Systems)
Abstract Background Undiagnosed depressive and anxiety disorders may be widespread. The study aimed to assess the prevalence and associated factors of undiagnosed depressive and/or anxiety disorders (DAD) among women in two low-resource countries, Bangladesh and Nepal. Methods Data were analyzed from 19,987 women (aged 15–49 years) in the 2022 Bangladesh Demographic and Health Survey and 7,442 women (aged 15–49 years) in the 2022 Nepal Demographic and Health Survey who completed the interview-administered nationally representative sub-survey component on mental health. DAD was categorized as either ‘undiagnosed DAD’ (meeting symptom criteria on the PHQ-9 and/or GAD-7 but without a prior diagnosis or treatment) or ‘diagnosed DAD’ (having a prior diagnosis and/or current treatment). Relative to diagnosed DAD, associations with undiagnosed DAD were estimated using logistic regression. Results The analytic sample included 2,388 women in Bangladesh and 960 women in Nepal with undiagnosed DAD and diagnosed with DAD. The prevalence of undiagnosed DAD was 44.8% in Bangladesh and 60.0% in Nepal. In Bangladesh, in adjusted logistic regression analysis, having a big problem with permission to go to a health facility (Adjusted Odds Ratio-AOR: 1.53, 95% Confidence Interval (CI): 1.21–1.93, p < 0.001), being widowed (AOR: 2.04, 95% CI: 1.40–2.99, p < 0.001) and being divorced or separated (AOR: 2.30, 95% CI:1.40–3.77, p < 0.001) were significantly positively associated with undiagnosed DAD. Having secondary or higher education (AOR: 0.75, 95% CI: 0.58–0.97, p = 0.028) was significantly negatively associated with undiagnosed DAD. In Nepal, compared to the rich or richest wealth status, poor or poorest wealth status (AOR: 1.55, 95% CI: 1.09 to 2.21), compared to Bramin/Chhetri ethnicity, being Dalit (AOR: 1.77, 95% CI: 1.08–2.89) and being Janajati (AOR: 1.72, 95% CI: 1.17–2.54) were positively associated with undiagnosed DAD. Increasing age (AOR: 0.97, 95% CI: 0.96–0.99) was negatively associated and history of cervical cancer screening (AOR: 0.57, 95% CI 0.32–1.02) was marginally negatively associated with undiagnosed DAD. Conclusion Nearly half of the women in Bangladesh and three in five women in Nepal had undiagnosed DAD. Targeted interventions addressing these factors are needed to improve mental health screening and access to care for women in Bangladesh and Nepal.